The Efficacy of User Committees in the Sustainable Management of Micro-Drinking Water Systems - Durgaprasad, P.; Srinivasan, S. (Water Nepal, 2003)
National water resources are common property resources. Besides the state, the community also has a right to harness, conserve and use the water resources within its geographical boundaries without adversely affecting the neighbourhood. The rights of user communities must be well defined in order to make the communities judicious, accountable and efficient in matters of water management in general and in drinking water in particular. People’s movements such as the Pani Panchayats in Maharashtra, the Sukhomajari project in Haryana, the rainwater harvesting interventions of Anna Hazare in Maharashtra and Rajender Singh’s Water Parliaments in Rajasthan are illustrative of the spirit of the collective rights and responsibilities of communities with regard to the management of water resources for irrigation as well as for drinking. Treating water as a common good is the route to sustainability in water use and democratic control for ensuring water rights for all. Privatisation is not the answer to the water crisis because it strengthens the not-so-positive ecological and political processes which have brought it about. While the concept of commons is based on the inalienability of shared rights derived from use, privatisation is based on the tradability of private property (Shiva, 2000). The paper highlights the lessons drawn from an Indian field study on community-based initiatives in governance, rights to water, conservation, augmentation and management, which are part of a partnership between communities and NGOs in ensuring the equitable distribution and quality control of drinking water. When it was discovered that excess fluoride in the drinking water was a major problem in Mehsana District of Gujarat, India, the local community of the village Meta in cooperation with an NGO embarked upon an innovative community-based intervention to install a mini defluoridation-based drinking water plant. A system of augmenting and rationing quality of drinking water for all was evolved with the aim of conserving drinking water as well as pricing it in such a manner that the water users themselves pay for the operation and maintenance of the plant. The focus was on community capacity building and sustainability. The paper also highlights critical matters related to institutional governance and the limitations of state run rural water supply systems. Pricing alone will not be a sustainable solution and attention needs to be paid to community rights to water as well as to their ability to pay for it. Water Nepal Vol.9-10, No.1-2, 2003, pp.337-348